UPAYA PENINGKATAN KEMAMPUAN BERPIKIR KRITIS SISWA KELAS V MIN 4 KOTA LHOKSEUMAWE DALAM MATA PEMBELAJARAN BAHASA INDONESIA PADA MATERI TEKS NONFIKSI MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW - Sukmawati; Almuhajir; Samsul Bahri (STKIP Subang, 2026)
This study was carried out because fifth-grade students at MIN 4 Kota Lhokseumawe showed low critical thinking skills when learning Indonesian, especially with non-fiction texts. The study focused on explaining how the Jigsaw cooperative learning model is used and looked at how it helps enhance students' critical thinking abilities. This research employed a qualitative descriptive approach. The study focused on fifth-grade students and their classroom teacher. Information was gathered by watching, talking to people, and looking at documents. The results showed that using the Jigsaw cooperative learning model helped students get involved in learning activities, talk about ideas together, share their thoughts confidently, and examine information carefully. Students showed progress in various aspects of critical thinking. This included understanding information, breaking down text, judging arguments, reaching logical conclusions, and clearly explaining their ideas. Also, the learning environment turned into a place where students worked together more, interacted with each other, and focused on their own needs. However, some challenges were found, like the differences in how students learn and the lack of control in the classroom during group discussions. In general, the Jigsaw cooperative learning model showed that it was helpful in enhancing students' critical thinking skills while learning the Indonesian language, particularly with non-fiction texts. So, this model can be seen as a different way to help students learn and have engaging and meaningful learning experiences in elementary school.